Sustainable urban public transportation system in Malaysia: a comparison of bus services in Kuantan and Penang - Ponrahono, Zakiah; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor (2016)
Transportation refers to the mobility of activities and goods from all economic sectors. Transportation is the key towards sustaining goods, services and people mobility in economic activities. Public buses in Malaysia, in general, and Kuantan and Penang, in particular, have faced many challenges, including dwindling number of passengers. This research focuses on the passengers’ perspective of the bus services from the aspects of frequency, travel time, as well as comfort and convenience. It aims at analysing passengers’ aspiration and perspectives of sustainable urban public transport and focuses on the assessment of Malaysian urban bus services within selected areas in Kuantan and Penang. Satisfaction of the current patronage is assessed against several measurements. Buses function as feeders to these socioeconomic traffic generators on a daily basis, especially for commuters. Thus, comparison of sustenance of passengers is also made of both Kuantan and Penang users. The research found that some socio-demographic and trip characteristics indeed influenced the current satisfaction level of the passengers. Recommendations have been made to the bus operators to ensure future sustainability of urban stage bus services in Kuantan and Penang.